Peran Lingkungan Berbahasa dalam Meningkatkan Keterampilan Berbicara Bahasa Arab di PKBM Ibnu Abbas School - Abdillah, Hafiz; Alawiyah, Lalah; Matin, Iman (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
This research is motivated by a unique phenomenon at PKBM Ibnu Abbas School, where elementary school students can speak Arabic fluently despite the school not being a pesantren. This condition is intriguing to study as it is rare to find elementary schools that successfully create a consistent Arabic-speaking environment. The main issue addressed in this research is how the school environment can support the development of students' Arabic-speaking skills. This study aims to describe the implementation of the Arabic-speaking environment at PKBM Ibnu Abbas School, both inside and outside the classroom, analyze the influence of this environment on students' speaking skills, and identify supporting and inhibiting factors in the development of Arabic-speaking skills. The research uses a qualitative method with a descriptive approach. Data collection was conducted through direct observation, interviews with teachers, and documentation. The research subjects were fifth-grade students, focusing on the practice of using Arabic in various school activities. The results showed that the implementation of the Arabic-speaking environment at PKBM Ibnu Abbas School is highly effective. Teachers, staff, and students actively use Arabic in daily communication. Supporting factors include proactive school policies, teacher involvement in modeling Arabic use, the use of learning media such as posters and videos, and the application of the immersion method. Meanwhile, inhibiting factors consist of students' limited vocabulary and the influence of the dominant use of the mother tongue outside the school environment. This research concludes that the success of developing Arabic-speaking skills at PKBM Ibnu Abbas School is supported by a conducive Arabic-speaking environment, reinforced by school policies, and active interaction between teachers, staff, and students.